ANALISIS KEBUTUHAN AIR BERSIH MASYARAKAT KECAMATAN PETANG - I Komang Angga Darmayasa; Putu Aryastana; Anak Agung Sagung Dewi Rahadiani (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2018)
ABSTRACT Requirement for aw water supply will increase every year as the population increases. Analysis of water requirements in Petang District is carried out using the leastsquare method with a projection of 25 years. The results of the analysis show that the compliance of water in Petang District has a devicit in Sulangai Village. Planning the addition of a water source of 7.68 liters per second in Sulangai Village by optimizing the Sulangai Atas II Spring. Network schema planning is analyzed using WaterNet. The results of the pipeline simulation show that there is no problem with the water supply system for the Petang Subdistrict area which means that hydraulically the network can serve the water needs of each service area. Keywords: Network, Pipe, Requirement, Water, WaterNet